An efficient and quantitative assay for epitope-tagged therapeutic protein development with a capillary western system. (20th March 2019) - Li, Yong; Duah, Ernest; Long, Nick; Persaud, Avinash; VanGundy, Zachary; Magliery, Thomas; Poi, Ming J
Aim: To develop and validate a reliable, robust and efficient assay to detect and quantify biologic compounds in vitro and in vivo during early stage of a biotherapeutic agent discovery.Methodology & results: An enrichment-free immunoassay method was developed to quantify a polyhistidine N- and FLAG C-terminally-tagged recombinant protein of ∼55 kDa. The target proteins were purified by a nickel-based matrix via tag affinity, followed by probing with biotinylated antitag antibody and subsequently detected by streptavidin-horseradish peroxidase conjugate using an automated capillary-based western system.Conclusion: A simple, highly sensitive and efficient immunoassay protocol was established to assess the in vitro stability and pharmacokinetic properties of propitious recombinant proteins in vivo in mouse to support early stage development of a biotherapeutic lead.